2020
DOI: 10.26434/chemrxiv.12902288
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assigning the Origin of Microbial Natural Products by Chemical Space Map and Machine Learning

Abstract: <p>Microbial natural products (NPs) are an important source of drugs. However, their structural diversity remains poorly understood. Here we used our recently reported MinHashed Atom Pair fingerprint with diameter of four bonds (MAP4), a fingerprint suitable for molecules across very different sizes, to analyze the Natural Products Atlas (NPAtlas), a database of 25,523 NPs of bacterial or fungal origin downloaded from <a href="https://www.npatlas.org/joomla/">https://www.npatlas.org/joomla/</a&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…TMAP was used in the global analysis of the peptide chemical space, whereas MAP4 was employed as the molecular representation of peptides [47]. A similar approach was used to visualize the chemical space of NPs in the public domain [53]. To assist the processes of decision-making and selecting compound libraries for further virtual screening or compound acquisition for high-or medium-throughput screening for epigenetic drug discovery, Flores-Padilla et al reported a comprehensive analysis of 11 commercial libraries of varying sizes focused on epigenetic targets (with 53,443 compounds in total) [48].…”
Section: Molecular Diversitymentioning
confidence: 99%
“…TMAP was used in the global analysis of the peptide chemical space, whereas MAP4 was employed as the molecular representation of peptides [47]. A similar approach was used to visualize the chemical space of NPs in the public domain [53]. To assist the processes of decision-making and selecting compound libraries for further virtual screening or compound acquisition for high-or medium-throughput screening for epigenetic drug discovery, Flores-Padilla et al reported a comprehensive analysis of 11 commercial libraries of varying sizes focused on epigenetic targets (with 53,443 compounds in total) [48].…”
Section: Molecular Diversitymentioning
confidence: 99%
“…The ISIDA descriptors have also been used to explore the chemical space of natural product. MinHashed Atom Pair fingerprint with diameter of four bonds (MAP4) was reported as a molecular fingerprint with good performance in similarity searching and chemical space visualization for different molecular sizes, which were analyzed in Natural Products Atlas (NPAtlas) containing microbial origins ( Capecchi et al, 2020 ; Capecchi and Reymond, 2020 ). These could be great ideas for conducting experimental research using natural product databases, molecular descriptors and fingerprints, chemical space navigation of natural product against COVID-19.…”
Section: Chemical Cartography or Chemography Approachesmentioning
confidence: 99%
“…258 An analysis of 25,523 natural isolates from fungi and bacteria (NatProdAtlas) revealed new distinctions of evolutionary origin based on their structures and biosynthetic pathways. 259 Using a dataset of 201,791 natural products in comparison with the same number of synthetic products, a machine learning algorithm developed parameters for distinguishing the 2 sets with high accuracy and quantifying natural product-likeness. As expected, the space occupied by the natural products and the overall diversity and complexity (eg, stereocenters) was much larger for the natural products, the number of nitrogen atoms was smaller, and the number of oxygen atoms greater.…”
Section: Machine Learningmentioning
confidence: 99%